Análise da prática didática sobre o uso da literatura no ensino de história - Toscano, Otávio Benincá (2022)
The work “Analysis of didactic practice using literature in history teaching” focuses in analyzing how the use of literature helps constructing school history knowledge. Based in these objective, two applications were developed with high school students from private schools of São Mateus/ES. The applications were made using two books, “Panelinha de Breu” (1992) and “A Capitoa” (2014) by the capixaba author Bernadette Lyra. A metaphor from Bernadette speech has been used:”The life of a woman is made by three lives: the one people say she had, the one she could have had, but the one she did have will be never known, indeed” (Lyra, 2014). The author intends, with this quote, to show that the memory of tne women she tries to portrait could be represented for both literature and history. “The one they say she had”, belongs to the history field, made by documents, photographs, journals, books, a narrative. “The one she could have had”, is due to literature, which creates plots with absence of details. “The one she did have, in fact, is the everyday life which will never be represented in written way for no one. The purpose of this work is to remake Bernadette’s characters history, searching in what was possible to recompose the path of characters, culminating in a minibiography organization. In addition, it represents the characters in fictional stories. In both narratives, students appropriated both the historiographical production and the fictional books of Bernadette; they used through the narratives the issues about women’s role in society and history, they understood the difference between history and literary production, they made fictional works in which they could work the concepts of anachronism and denialism. The conclusion reached was that the use of literature as a resource combined with historical documents transformed into didactic materials showed great potential as a teaching strategy.